2004
DOI: 10.1039/b310238f
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized generation of singlet oxygen from ruthenium(ii) and osmium(ii) bipyridyl complexes

Abstract: Photophysical properties for a number ruthenium(II) and osmium(II) bipyridyl complexes are reported in dilute acetonitrile solution. The lifetimes of the excited metal to ligand charge transfer states (MLCT) of the osmium complexes are shorter than for the ruthenium complexes. Rate constants, kq, for quenching of the lowest excited metal to ligand charge transfer states by molecular oxygen are found to be in the range (1.1-7.7) x 10(9) dm3 mol(-1) s(-1). Efficiencies of singlet oxygen production, fDeltaT, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 55 publications
4
70
0
Order By: Relevance
“…They more than double when the solution is nitrogen flushed, consistent with energy transfer quenching of the excited state by dissolved molecular oxygen (3O 2 ), as shown previously for other Cr(III) complexes. [37][38] Rate constants for quenching by oxygen (kq) 39 calculated using an oxygen concentration of 288 mM (20 C) are collected in Table 1. 40 The lifetimes in both aerated and degassed solution are slightly longer for the triflate salt, possibly indicative of weak quenching by chloride as has been suggested by Neshvad et al 41 The emission lifetime of each complex in aerated solution was found to decrease when its concentration was increased.…”
Section: Transient Emission Measurementsmentioning
confidence: 99%
“…They more than double when the solution is nitrogen flushed, consistent with energy transfer quenching of the excited state by dissolved molecular oxygen (3O 2 ), as shown previously for other Cr(III) complexes. [37][38] Rate constants for quenching by oxygen (kq) 39 calculated using an oxygen concentration of 288 mM (20 C) are collected in Table 1. 40 The lifetimes in both aerated and degassed solution are slightly longer for the triflate salt, possibly indicative of weak quenching by chloride as has been suggested by Neshvad et al 41 The emission lifetime of each complex in aerated solution was found to decrease when its concentration was increased.…”
Section: Transient Emission Measurementsmentioning
confidence: 99%
“…7). In this context, it is probably also worth mentioning that certain Os metal-ligand complexes are toxic [143,144], but according to recent investigations, the toxicity and phototoxicity of Os complexes are comparable with Ru and Rh MLCs [145][146][147].…”
Section: Metal-ligand Complexesmentioning
confidence: 99%
“…The complex [(bpy) 2 Ru(dpp)] 2+ (where dpp = 2,3-bis(2-pyridyl)pyrazine) has been shown to photochemically generate singlet oxygen ( 1 O 2 ) [14]. Excitation of [(bpy) 2 Ru(dpp)] 2+ at 465 nm produces the 3 MLCT state with unit efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation of [(bpy) 2 Ru(dpp)] 2+ at 465 nm produces the 3 MLCT state with unit efficiency. The 3 MLCT state is quenched by oxygen to produce 1 O 2 with U = 0.31 ± 0.2 (in air equilibrated acetonitrile) [14]. The ability of [(bpy) 2 Ru(dpp)] 2+ to produce singlet oxygen has been examined though the characteristic emission of 1 O 2 at 1270 nm [14].…”
Section: Introductionmentioning
confidence: 99%